2020
DOI: 10.1097/scs.0000000000007198
|View full text |Cite
|
Sign up to set email alerts
|

Paradigm Shift in Airway Management for Pierre Robin Sequence: Tongue Base Suspension

Abstract: Surgical management of the airway in children with Pierre Robin Sequence (PRS) includes tongue lip adhesion and mandibular distraction. Herein, the authors report the first case of an alternative surgical approach, the tongue base suspension (TBS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…TBS has not been previously described in the treatment of children with PRS. They show that TBS can be a potential method for treating airway obstruction in neonates with PRS 11 . We also advocate that the role of TBS may be more important in TLA by assessing the effectiveness of TBS using intraoral endoscopy.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…TBS has not been previously described in the treatment of children with PRS. They show that TBS can be a potential method for treating airway obstruction in neonates with PRS 11 . We also advocate that the role of TBS may be more important in TLA by assessing the effectiveness of TBS using intraoral endoscopy.…”
Section: Discussionmentioning
confidence: 92%
“…Safri et al 11 reported the first use of TBS for this purpose. TBS may be considered an alternative in future surgical algorithms for managing the PRS, as it directly addresses the site of upper airway obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12,13] In addition, it is worth noting that due to airway dysfunction, children need to further strengthen the oxygen support for before and after mandibular traction. [14,15] At present, in clinical practice, after the child is weaned from the ventilator, a nasal cannula is usually used for additional oxygen support to meet the oxygen demand. Safe and effective oxygen support is very important for the prognosis of children with Pierre-Robin syndrome.…”
Section: The Authors Have No Funding and Conflicts Of Interest To Dis...mentioning
confidence: 99%
“…To the Editor: We read with great enthusiasm the recent publication by Safri et al (2020) proposing an innovative alternative surgical approach, tongue base suspension (TBS), for management of airway obstruction secondary to retrognathia, micrognathia, and glossoptosis in the patients with Pierre Robin sequence (PRS) 1 . Although we congratulate the authors for their successful management of the presented case of a 5-week-old full term male patient with PRS, we do not agree that presenting a single case should be considered as an example for a “paradigm shift” in the current status of airway management for PRS patients.…”
mentioning
confidence: 99%